Tetraspanin CD82 affects migration, attachment and invasion of rheumatoid arthritis synovial fibroblasts. Issue 11 (6th July 2018) - Neumann, Elena; Schwarz, Maria C; Hasseli, Rebecca; Hülser, Marie-Lisa; Classen, Simon; Sauerbier, Michael; Rehart, Stefan; Mueller-Ladner, Ulf
Abstract : Tetraspanins function as membrane adaptors altering cell-cell fusion, antigen presentation, receptor-mediated signal transduction and cell motility via interaction with membrane proteins including other tetraspanins and adhesion molecules such as integrins. CD82 is expressed in several malignant cells and well described as tumour metastasis suppressor. Rheumatoid arthritis (RA) is based on persistent synovial inflammation and joint destruction driven to a large extent by transformed-appearing activated synovial fibroblasts (SF) with an increased migratory potential. Objective: CD82 is upregulated in RA synovial fibroblasts (RASF) compared with osteoarthritis (OA) SF as well as within RA compared with OA synovial lining layer (LL) and the role of CD82 in RASF was evaluated. Methods: CD82 and integrin immunofluorescence was performed. Lentiviral CD82 overexpression and siRNA-mediated knockdown was confirmed (realtime-PCR, Western blot, immunocytochemistry). RASF migration (Boyden chamber, scrape assay), attachment towards plastic/Matrigel, RASF-binding to endothelial cells (EC) and CD82 expression during long-term invasion in the SCID-mouse-model were evaluated. Results: CD82 was induced by proinflammatory stimuli in SF. In RA-synovium, CD82 was expressed in RASF close to blood vessels, LL, sites of cartilage invasion and colocalised with distinct integrins involved in tumour metastasis suppression but also in RA-synovium by RASF. CD82 overexpression led to reduced RASF migration, cell-matrix and RASF-EC adhesion. Reduced CD82 expression (observed in the sublining) increased RASF migration and matrix adhesion whereas RASF-EC-interaction was reduced. In SCID mice, the presence of CD82 on cartilage-invading RASF was confirmed. Conclusion: CD82 could contribute to RASF migration to sites of inflammation and tissue damage, where CD82 keeps aggressive RASF on site.